Prevalência de cárie dentária em crianças de 6 e 12 anos de idade de escolas públicas do município de Maringá-PR - (:unkn) unknown (UNIVERSIDADE ESTADUAL DE PONTA GROSSA, 2004)
In order to contribute to the epidemiological surveillance process and indeed to diagnose the real condition of oral health of public school children in the city of Maringá, Parana State, Brazil, it was conducted this research. The prevalence of dental caries was evaluate using systematic random sample which was constituted by 610 subjects, both genders, living in the urban cluster.The methodology was based on the SB Brazil Project – Conditions of Buccal Health of the Brazilian Population. It was used diagnosis criteria of the World Health Organization (WHO), which included permanent and deciduous teeth. The Kappa Test indicated concordance in two levels (good and very good) inter and intra examiners. The mean dmf-t and DMF-T indexes were 1,8 and 1,5, respectively. The decay mean present in decayed deciduous teeth higher (1,0) than in filled tooth (0,7), while referring to permanent teeth, the filled teeth presented higher (1,1) than the decayed teeth (0,4). The lost component “M” was not significant in both ages and revealed a positive tendency of the odontological services in maintaining permanent and deciduous teeth. At 6 years, 47,7% of children (30,8% dmf-t index of 1 to 3, 17,3% of 4 to 7 and 4,3% higher numbers) and at 12 years, 50% of children (33,2% with DMF-T index of 1 to 3, 21,6% of 4 to 7 and 2,1 higher numbers) were caries free. When the polarization phenomenon was confirmed, 21,6% and 23,7% of school children concentrated major rates of disease. At 12 years, the children presented a statistically significant difference (p<0.05) among genders, where boys presented superior DMF-T index. The comparison of the dental decay distribution between municipal and state schools did not identified statistically significant differences in the dmf-t index, but on the contrary, this differences were observed to DMF-T index .The comparison of the results in this study with epidemiological researches made in the same city in previous years (1991 and 1994), showed an effective reduction in the decay prevalence to 12 years children, although at 6 years old this same prevalence was not observed. It was concluded the oral health of school children of this evaluated sample is in accordance to the objectives proposed by the World Health Organization to the year of 2000, presenting low prevalence of decay and the continuity of the educational and prevention programs is essential to reach the projected goals to the year of 2010.
Keywords: cárie dentária; epidemiologia; índice CPO; índice ceo; dental carie; epidemiology; DMF index; dmf index.; CNPQ::CIENCIAS DA SAUDE::ODONTOLOGIA